Neutrophil Elastase and Chronic Lung Disease - Judith A. Voynow; Meagan Shinbashi (Biomolecules, 2021)
Neutrophil elastase (NE) is a major inflammatory protease released by neutrophils and is present in the airways of patients with cystic fibrosis (CF), chronic obstructive pulmonary disease, non-CF bronchiectasis, and bronchopulmonary dysplasia. Although NE facilitates leukocyte transmigration to the site of infection and is required for clearance of Gram-negative bacteria, it also activates inflammation when released into the airway milieu in chronic inflammatory airway diseases. NE exposure induces airway remodeling with increased mucin expression and secretion and impaired ciliary motility. NE interrupts epithelial repair by promoting cellular apoptosis and senescence and it activates inflammation directly by increasing cytokine expression and release, and indirectly by triggering extracellular trap release and exosome release, which magnify protease activity and inflammation in the airway. NE inhibits innate immune function by digesting opsonins and opsonin receptors, degrading innate immune proteins such as lactoferrin, and inhibiting macrophage phagocytosis. Importantly, NE-directed therapies have not yet been effective in preventing the pathologic sequelae of NE exposure, but new therapies are being developed that offer both direct antiprotease activity and multifunctional anti-inflammatory properties.